DECIDING BY DISCRETIONARY POWER ON APPLICATION FOR ADMISSION TO THE CITIZENSHIP OF THE REPUBLIC OF SERBIA – THE LIMITS OF THE CONSTITUTIONAL CONTROL - Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The paper analyzes the boundaries of constitutional normative control of law provisions which authorize the administrative authorities to decide cases on discretionary power. The reason for this analysis is an example of the practice of the Constitutional Court of Serbia which tested the constitutionality of provision of the Law on Citizenship of the Republic of Serbia. Provision that was the subject of constitutional normative control included deciding on the application for admission or termination of citizenship on the base of discretionary power of the Ministry of Interior. The aim of analysis is to point out the failures and problematic places in the Court’s decision in the sense of omitting the essential issues relevant to the subject of the proceedings; the missing sharpness of legal arguments on which decision was based; the insufficient clarification of the Court in the respect of allegations of the initiative; and finally, and the most importantly, the lack of pointing on the nature and significance of the administrative act which is adopted on the base of discretionary power from the standpoint of general interest.